Computational fluid dynamics modelling of different detention pond configurations in the interest of sustainable flow regimes and gravity sedimentation potential. (2nd April 2014) - Tsavdaris, Alexandros; Mitchell, Steve; Williams, John B.
Abstract This study presents the results of the flow regime evaluation, by means of computational fluid dynamics (CFD), of a vegetated detention pond located at Waterlooville, Hampshire, UK. Alternative pond layouts were assessed for the same flow conditions on the basis of recommendations made in the literature. The results were validated by comparing the maximum computational velocities for the same case using different numbers of mesh elements. It was found that the development of a CFD model of detention ponds is intricate but feasible. The main findings were: (i) The present design performed well in terms of flood risk management, but the flow patterns could result in questionable treatment efficiency; (ii) vegetation seems to promote horizontal recirculation and turbulence; (iii) triangular and elliptical pond designs showed very poor performance; (iv) the most appropriate design for the given location and hydrological regime is an elliptical pond with a central emergent/submerged island.